2020
DOI: 10.3390/insects11080482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Life History and Parasitization Behavior of Trichogramma achaeae Nagaraja and Nagarkatti (Hym.: Trichogrammatidae)

Abstract: Trichogramma achaeae Nagaraja and Nagarkatti (Hymenoptera: Trichogrammatidae) is currently used as biological control agent for several lepidopteran pests. Knowledge of thermal requirements is essential to optimize its rearing procedures and inundative releases. The biological characteristics and two-sex life table parameters of T. achaeae were determined at five constant temperatures (15, 20, 25, 30, and 35 °C) using Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs. T. achaeae was able to develop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 76 publications
4
20
2
Order By: Relevance
“…Knowing how laboratory measurement of performance links to field efficacy may enhance quality control for BCAs and guide field applications. Previous studies on laboratory performance of T. achaeae demonstrated that several life history parameters (longevity, developmental time, sex ratio, body size, and fecundity) were strongly affected by temperature [ 24 , 31 ], and that fecundity best represented the overall laboratory performance [ 24 ]. In the microcosm study presented here, we show that the realised parasitisation ability in a microcosm was significantly influenced by temperature, similarly to that found for fecundity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowing how laboratory measurement of performance links to field efficacy may enhance quality control for BCAs and guide field applications. Previous studies on laboratory performance of T. achaeae demonstrated that several life history parameters (longevity, developmental time, sex ratio, body size, and fecundity) were strongly affected by temperature [ 24 , 31 ], and that fecundity best represented the overall laboratory performance [ 24 ]. In the microcosm study presented here, we show that the realised parasitisation ability in a microcosm was significantly influenced by temperature, similarly to that found for fecundity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower temperature threshold for T. telengai pre-imaginal development obtained in our experiments (about 5°C) is lower than those observed in other Trichogramma species: about 8°C for T. brassicae (Negahban et al, 2021), 9-12°C for T. chilonis (Haile et al, 2002;Ghosh et al, 2017), 9.2°C for T. evanescens (Haile et al, 2002), 9.3°C for T. cordubensis (Ghosh et al, 2017), 10°C for T. buesi (Reznik et al, 2009), 10-11°C for T. pretiosum and T. annulata (Maceda et al, 2003;de Oliveira et al, 2017;Zuim et al, 2017), 10.3-14.5°C for T. japonicum (Ruan et al, 2018;Ghosh et al, 2017), about 10.5°C for T. achaeae (del Pino et al, 2020), 10.7°C for T. ostriniae (Wang et al, 2004), 11.8°C for T. turkestanica and T. principium (Hansen, 2000;Reznik & Voinovich, 2015), 12.0°C for T. kaykai (Hohmann & Luck, 2000) and 13.6°C for T. galloi (Cônsoli & Parra, 1995). This difference can be possibly explained by that the studied strain of T. telengai originated from Moscow province, which is far to the north of geographic ranges of above listed species.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of temperature on various biological parameters of Trichogramma wasps were investigated by many authors (e.g. Chen et al, 2021;Cônsoli & Parra, 1995;Firake & Khan, 2014;Haile et al, 2002;Hansen, 2000;Hohmann & Luck, 2000;Negahban et al, 2021;de Oliveira et al, 2017;del Pino et al, 2020;Reznik & Voinovich, 2015;Ruan et al, 2018;Ghosh et al, 2017;Wang et al, 2004;Zuim et al, 2017). In particular, it is known that facultative (winter) pre-pupal diapause is induced by low temperature experienced by Trichogramma embryos and larvae.…”
Section: Introductionmentioning
confidence: 99%
“…chalcites eggs in Madeira, Azores, and Canary Islands [ 29 , 30 , 31 , 32 ]. Among them, T. achaeae Nagaraja and Nagarkatti has been reported as the most important species in the main banana-producing islands of the Canary archipelago [ 33 ], showing high potential as a biological control agent [ 34 ]. However, no studies have been published yet on the potential T. achaeae releases to suppress Ch.…”
Section: Introductionmentioning
confidence: 99%